COX-2 Docking Structural Analysis with Phytochemical Extracts of Rosemary: A Possible Cytotoxicity on Head and Neck Squamous Cell Carcinoma Cell Line (HEp-2) - Abd El-Hamid, Ihab S.; Mouselhy, Yara Y.; El-Shafei, Marwa M.; Sayed, Marwa M.; Mohamed, Aly F.; Farag, Doaa B. (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: Various phenolic phytochemical extracts have been claimed to exhibit different types of biological activity, including anti-inflammatory, anti-oxidative and anti-carcinogenic activity. Carnosol and carnosic acid, extracts of rosemary, are among these phenolic compounds. Materials and Methods: CHARMm-based molecular docking was performed to estimate the possible molecular interactions of both carnosic acid and carnosol with the COX-2 active binding site. An MTT assay was used to evaluate HEp-2 cell viability after incubation for 48 hours with low or high concentrations of carnosol, carnosic acid or their combination. The levels of COX-2 were measured in cell lysate by the quantitative indirect ELISA technique. Results: Docking revealed favourable negative binding energies as well as binding interactions of both carnosic acid and carnosol within the binding site of the COX-2 receptor. Carnosic acid showed more favourable binding potential than carnosol. One-way ANOVA and Bonferroni’s post hoc tests revealed significant differences in cytotoxicity among cells treated with different concentrations of the rosemary extracts (P< 0.001). ELISA revealed significant reductions in COX-2 protein levels in HEp-2 cells treated with either carnosic acid (-1.42- fold) or carnosol (-3.16-fold) compared to control cells. Conclusion: Both rosemary extracts, carnosol and carnosic acid, exert potential cytotoxic effects on the HEp-2 cell line via inhibition of the COX-2 pathway. The combination of carnosol and carnosic acid exerts a stronger cytotoxic effect than either compound alone.
Keywords: carnosic acid